Resistance of Shifting Cultivators: Analysis of Adaptation and Resistance Strategies in Routa, Indonesia - Sarlan Adijaya (Journal of Law, Social Science and Management, 2025)
Background: The changing orientation of shifting cultivators in the Routa region of Southeast Sulawesi reflects complex socio-ecological dynamics shaped by the expansion of agrarian capitalism. The transition from traditional dryland rice farming to broader dryland land use represents a transformation in farmers’ livelihood strategies in response to state interventions and capitalist pressures. Objectives: This study aims to examine the forms of resistance adopted by shifting cultivators in Routa in response to inequalities in natural resource governance, and to identify the underlying strategies and motivations driving changes in cultivation practices. Methods: Employing a qualitative research design, this study applies the theoretical framework of peasant resistance. Data were collected through in-depth interviews, participant observation, and analysis of local documents. Results: The findings reveal that the shift toward swidden agriculture serves as a rational strategy to secure land and resource access. Resistance is expressed in latent forms through adaptive cultivation practices, avoiding overt confrontation while implicitly challenging state authority and capitalist control. Conclusion: This study contributes to a deeper understanding of contemporary agrarian resistance by highlighting how strategic rationality underpins local responses to capital expansion in rural contexts. The findings underscore the significance of everyday forms of resistance in sustaining agrarian livelihoods. Keywords: Shifting cultivation; peasant resistance; adaptation strategies; agrarian capitalism; land access; Routa